Pengaruh Pengambilan Risiko Terhadap Niat Berwirausaha (Studi Pada Mahasiswa Penerima PMW Undiksha Tahun 2022) - Saragih, Novri Sertika; Santi, Ni Wayan Ayu (Universitas Pendidikan Ganesha, 2025)
This research aims to determine the influence of risk-taking variables on the entrepreneurial intentions of students receiving PMW Undiksha in 2022. This research is a type of causal quantitative research and sampling is based on probability sampling with cluster sampling techniques. The population in this study were students who received PMW Undiksha in 2022. The sample used was students who received PMW Undiksha in 2022, totaling 117 students. The data collection method uses a questionnaire which is measured using a Likert scale. Data processing uses the SPSS version 26 program for Windows. The data analysis technique used is simple linear regression analysis with partial hypothesis testing (t test) and classical hypothesis testing. The research results show that risk taking has a positive and significant effect on entrepreneurial intentions. Partial risk taking has a positive and significant effect on entrepreneurial intentions, with a significant value of 0.000 < 0.05.